Innovation of Energy Technologies of Food Raw Material Dehydration and Extraction - Burdo O.G.; Sirotyuk I.V; Shcherbich M.V.; Akimov A.V.; Poyan A.S. (Problems of the Regional Energetics, 2021)
The researchings of raw material dehydration and extraction are analyzed. The energy problems of product dehydration processes are analyzed. It is shown that recent trends in the development of heat and mass transfer technology are associated with the use of electromagnetic energy gen-erators. The aim of the work is reduction of energy consumption during liquid phase removing from solid plant raw material and reduction of product losses from oil-containing food-industry waste. Achievement of this aim lies with a hypothesis that the use of electromagnetic energy sources in the process of removing moisture from food raw material containing a solid phase will allow to form an additional flow of the liquid phase, in addition to the traditional outlet of the vapor phase. The driving force of such a flow is the effect resulting from the local dissipa-tion of electromagnetic energy in the solid phase volume. A mathematical model of the dehydra-tion process is presented and a set of experimental studies was carried out, which confirmed the validity of the hypothesis. The most significant result of the work is proof of the possibility to organize modes when the juice yield is 4 times higher than the steam yield and, accordingly, to reduce energy consumption for product dehydration. The scientific significance of the obtained results is that a new effect was obtained in the work, which the authors called parodynamic. The practical significance of the work consists of proposing of the technological line for processing oil-containing waste: coffee sludge, coffee beans husk, reagents (clay and perlite).